A high-density N-doped carbon-based iron single-atom catalyst and its preparation method and application
The high-density N-doped carbon-based iron single-atom catalyst was prepared by metal coordination grinding-high temperature cracking method, which solved the problem of low density of metal active sites of existing catalysts, and achieved efficient degradation of antibiotics and improved catalytic performance.
Patent Information
- Application Number
- CN202410076724.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-01-18
AI Technical Summary
The low density of metal active sites of existing single-atom catalysts leads to limited catalytic capacity, limiting their application in treating antibiotic wastewater.
The high-density N-doped carbon-based iron single-atom catalyst was prepared by metal coordination grinding-high temperature cracking. The density of the metal active center was improved by combining ball milling-high temperature pyrolysis.
It has achieved efficient degradation of new pollutants such as antibiotics, and has strong catalytic capacity, high degradation efficiency and short time to avoid secondary pollution of pollutants.
Smart Images

Figure CN118022803B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a high-density N-doped carbon-based iron single-atom catalyst and a preparation method and application thereof. Background Art
[0002] Antibiotics, persistent organic pollutants, endocrine disruptors and microplastics are known as the four major types of new pollutants. Due to the extensive use of antibiotics and unreasonable discharge methods, the content of antibiotics in surface water, groundwater and soil will exceed the standard. Even if low concentrations of antibiotics are discharged into the environment, it will pose a huge environmental risk. Antibiotics are difficult to be effectively removed by traditional treatment technologies due to their non-degradability and strong stability. Deep treatment technologies are urgently needed for treatment. Compared with other advanced oxidation technologies, persulfate oxidation technology is widely used in the treatment of antibiotic wastewater because it is not restricted by pH, has high catalytic activity and strong persistence of active species.
[0003] As scientists delve deeper into persulfate technology, the single-atom catalyst-persulfate heterogeneous oxidation technology combines the advantages of both traditional persulfate homogeneous oxidation technology and persulfate heterogeneous oxidation technology, showing the advantages of ultra-high catalytic activity, high atom utilization and low catalyst usage.
[0004] For example, Chinese patent CN115301268A discloses a Fe-N4 active site single atom catalyst for selectively generating singlet oxygen by activating peroxydisulfate and its preparation method and application. The single atom catalyst of the present invention is prepared by high-temperature pyrolysis of two MOFs, NH2-MIL-53 and ZIF-8, as precursors; the catalytic center structure of the single atom catalyst is Fe-N4. The catalyst of the invention acts as an electron transfer mediator to activate peroxydisulfate (PDS) to generate singlet oxygen ( 1 O2) is used as an active species for degrading pollutants for the oxidative degradation of difficult-to-degrade organic pollutants. The catalyst prepared by the invention can resist the interference of environmental background factors and remain stable within a large pH range when degrading difficult-to-degrade organic pollutants in wastewater.
[0005] Another example is Chinese patent CN113058635A which discloses a method for activating persulfate to generate pure singlet oxygen ( 1 O2) single-atom catalyst and its preparation method and application. The single-atom catalyst of the invention includes a carrier and an iron single atom loaded on the carrier; the carrier is a graphite phase carbon nitride nanosheet; the iron single atom is bound to the carrier in a Fe-N4 coordination structure. The invention uses graphite phase carbon nitride nanosheets as carriers to make the surrounding environment of the iron single atom uniform, and when persulfate is activated, it is only converted into 1 O2, and1 O2 has good selectivity and anti-interference ability, which makes the single-atom catalyst provided by the invention have excellent selectivity and anti-interference when degrading organic pollutants. At the same time, the mass of the iron single atom in the single-atom catalyst is 7-12% of the mass of the single-atom catalyst, which improves the efficiency of the single-atom catalyst in activating persulfate.
[0006] However, in the development of single-atom catalysts, there are disadvantages of uneven distribution of active sites and low density of metal active centers. This may be because a single metal cannot be stably anchored on the surface of the carrier material (carbon-based materials, silica, ferroferric oxide, titanium dioxide, etc.), resulting in limited catalytic ability, which further limits the promotion and application of single-atom catalysts.
[0007] Therefore, it is necessary to develop a porous single-atom catalyst with a large specific surface area that can target new pollutants, antibiotics, and achieve efficient degradation in the presence of oxidants. Summary of the invention
[0008] Based on the problem of low density of metal active centers in single-atom catalysts in the prior art, a high-density N-doped carbon-based iron single-atom catalyst and its preparation method are provided. That is, a porous single-atom catalyst with a large specific surface area is prepared by adopting the method of metal coordination grinding-high temperature cracking, and new pollutant antibiotics are used as target pollutants to achieve efficient degradation in the presence of oxidants. Compared with the prior art / catalysts, the catalyst has the characteristics of strong catalytic ability, high pollutant degradation efficiency and short time consumption.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] On the one hand, the present invention provides a method for preparing a high-density N-doped carbon-based iron single-atom catalyst, that is, a single-atom Fe-N doped carbon catalyst (Fe SAs-NC) is synthesized by a method combining ball milling and high-temperature pyrolysis.
[0011] The specific steps include:
[0012] (1) adding ferrous sulfate, a surfactant, 2-methylimidazole and methanol into a ball mill and grinding to obtain an iron precursor mixture 1, centrifuging, washing and drying to obtain an iron precursor solid for later use;
[0013] (2) The iron precursor solid and melamine were mixed and added to an agate bottle, and then ground and passed through a 300-350 mesh sieve to obtain a mixture; the mixture was then heated in a nitrogen atmosphere at 5°C·min -1 The mixture was heated to 600°C at a rate of 100°C and calcined for 3-6 hours to obtain a mixture 2;
[0014] (3) The mixture 2 was washed with H2SO4 for 6 h to prepare a high-density N-doped carbon-based iron single atom catalyst, labeled as Fe SAs-NC x ;
[0015] Wherein, X is the weight ratio of the iron precursor to melamine, X=0.2, 0.1 or 0.05.
[0016] The surfactant is a mixture of sodium dodecyl sulfate and dodecyl mercaptan; preferably, the surfactant is sodium dodecyl sulfate and dodecyl mercaptan in a mass ratio of 3-5:1; more preferably, the surfactant is sodium dodecyl sulfate and dodecyl mercaptan in a mass ratio of 4:1.
[0017] Furthermore, the mass ratio of ferrous sulfate, surfactant and 2-methylimidazole described in step (1) is 1-3:5-10:4-8; preferably, the mass ratio of ferrous sulfate, surfactant and 2-methylimidazole is 2:8:6.
[0018] Furthermore, the mass ratio of the methanol to the ferrous sulfate is 8-12:1; preferably, the mass ratio of the methanol to the ferrous sulfate is 10:1; and the concentration of the methanol is 90-95%.
[0019] Furthermore, the grinding in step (1) is performed by grinding in a planetary ball mill for 120 minutes.
[0020] Furthermore, the mass ratio of the iron precursor solid to melamine in step (2) is 1:0.05-0.2; preferably, the mass ratio of the iron precursor solid to melamine is 1:0.05, 1:0.1 or 1:0.2.
[0021] Furthermore, the concentration of H2SO4 in step (3) is 30%-50%.
[0022] On the other hand, the present invention also provides a high-density N-doped carbon-based iron single-atom catalyst prepared by the above method.
[0023] On the other hand, the present invention also provides the use of the high-density N-doped carbon-based iron single-atom catalyst prepared by the above method in the process of degrading antibiotics.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) Solve the problem of low density of metal active sites in single-atom catalysts, and use the metal coordination grinding-high temperature cracking method to achieve stable anchoring of single metal atoms, greatly improving the density of metal active centers;
[0026] 2) Reduce the preparation cost of the catalyst. A small amount of solvent is used in the preparation process. The high coordination of the metal is completed under the action of physical grinding. There is no need to consume too much energy to treat the preparation waste, which greatly reduces the subsequent solvent treatment cost;
[0027] 3) Improve the catalytic performance of single-atom catalysts, take new pollutant antibiotics as target pollutants, use high-density single-atom catalysts, assisted by oxidants, to achieve efficient degradation and even mineralization of new pollutants, and avoid secondary pollution problems of pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a characterization diagram of the N-doped carbon-based iron single atom catalyst prepared in Example 5 of the present invention;
[0029] (a) TEM image of Fe SAs-NC catalyst; (b) SEM image; (c) high-resolution HAADF-STEM image of Fe SAs-NC catalyst; (d) HAADF-STEM image of Fe SAs-NC catalyst; (eg) EDS spectrum corresponding to Fe SAs-NC catalyst.
[0030] Figure 2 High-resolution (a) C1s and (b) Fe2p XPS spectra of the N-doped carbon-based iron single-atom catalyst prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0031] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present invention.
[0032] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0033] Example 1 Preparation method of a high-density N-doped carbon-based iron single-atom catalyst
[0034] The specific steps include:
[0035] (1) adding ferrous sulfate, a surfactant, 2-methylimidazole and 90% methanol into a ball mill and grinding the mixture at 600 rpm for 120 min using a planetary ball mill to obtain an iron precursor mixture 1, centrifuging, washing and drying the mixture to obtain an iron precursor solid for later use;
[0036] The mass ratio of ferrous sulfate, surfactant and 2-methylimidazole is 1:5:4; the mass ratio of methanol to ferrous sulfate is 8:1; the surfactant is sodium dodecyl sulfate and dodecyl mercaptan in a mass ratio of 3:1;
[0037] (2) The iron precursor solid and melamine were mixed and added to an agate bottle, and then ground and passed through a 300-mesh sieve to obtain a mixture; the mixture was then heated in a nitrogen atmosphere at 5°C / min -1 The temperature was raised to 600°C at a rate of 100 °C and calcined for 3 h to obtain a mixture 2;
[0038] Among them, the mass ratio of iron precursor solid to melamine is 1:0.05
[0039] (3) Mixture 2 was washed with 30% H2SO4 for 6 h to prepare a high-density N-doped carbon-based iron single atom catalyst, labeled as Fe SAs-NC 0.05 .
[0040] Example 2
[0041] The difference from Example 1 is that the mass ratio of the iron precursor solid to melamine is 1:0.1; the obtained high-density N-doped carbon-based iron single atom catalyst is marked as Fe SAs-NC 0.1 .
[0042] Example 3
[0043] The difference from Example 1 is that the mass ratio of the iron precursor solid to melamine is 1:0.2; the obtained high-density N-doped carbon-based iron single atom catalyst is marked as Fe SAs-NC 0.2 .
[0044] Example 4 Preparation method of a high-density N-doped carbon-based iron single-atom catalyst
[0045] The specific steps include:
[0046] (1) adding ferrous sulfate, a surfactant, 2-methylimidazole and 90% methanol into a ball mill and grinding the mixture at 600 rpm for 120 min using a planetary ball mill to obtain an iron precursor mixture 1, centrifuging, washing and drying the mixture to obtain an iron precursor solid for later use;
[0047] The mass ratio of ferrous sulfate, surfactant and 2-methylimidazole is 3:10:8; the mass ratio of methanol to ferrous sulfate is 12:1; the surfactant is sodium dodecyl sulfate and dodecyl mercaptan in a mass ratio of 5:1;
[0048] (2) The iron precursor solid and melamine were mixed and added to an agate bottle, and then ground and passed through a 300-mesh sieve to obtain a mixture; the mixture was then heated in a nitrogen atmosphere at 5°C / min -1 The temperature was raised to 600°C at a rate of 100°C and calcined for 6 hours to obtain a mixture 2;
[0049] Among them, the mass ratio of iron precursor solid to melamine is 1:0.2
[0050] (3) Mixture 2 was washed with 50% H2SO4 for 6 h to prepare a high-density N-doped carbon-based iron single atom catalyst, labeled as Fe SAs-NC 0.2 .
[0051] Example 5 A method for preparing a high-density N-doped carbon-based iron single-atom catalyst
[0052] The specific steps include:
[0053] (1) adding ferrous sulfate, a surfactant, 2-methylimidazole and 90% methanol into a ball mill and grinding the mixture at 600 rpm for 120 min using a planetary ball mill to obtain an iron precursor mixture 1, centrifuging, washing and drying the mixture to obtain an iron precursor solid for later use;
[0054] The mass ratio of ferrous sulfate, surfactant and 2-methylimidazole is 2:8:6; the mass ratio of methanol to ferrous sulfate is 10:1; the surfactant is sodium dodecyl sulfate and dodecyl mercaptan in a mass ratio of 4:1;
[0055] (2) The iron precursor solid and melamine were mixed and added to an agate bottle, and then ground and passed through a 300-mesh sieve to obtain a mixture; the mixture was then heated in a nitrogen atmosphere at 5°C / min -1 The temperature was raised to 600°C at a rate of 100°C and calcined for 5 hours to obtain a mixture 2;
[0056] Among them, the mass ratio of iron precursor solid to melamine is 1:0.2
[0057] (3) Mixture 2 was washed with 40% H2SO4 for 6 h to prepare a high-density N-doped carbon-based iron single atom catalyst, labeled as Fe SAs-NC 0.2 .
[0058] Comparative Example 1
[0059] The difference from Example 5 is that the surfactant is replaced by polyvinyl pyrrolidone.
[0060] Comparative Example 2
[0061] The difference from Example 5 is that the surfactant is only sodium lauryl sulfate.
[0062] Comparative Example 3
[0063] The difference from Example 5 is that the surfactant is only dodecyl mercaptan.
[0064] Comparative Example 4
[0065] The difference from Example 5 is that the mass ratio of sodium dodecyl sulfate to dodecyl mercaptan is 1:1.
[0066] Comparative Example 5
[0067] The difference from Example 5 is that the mass ratio of sodium dodecyl sulfate to dodecyl mercaptan is 6:1.
[0068] Experimental Example 1: Characterization of Single Atom Catalysts
[0069] The original NC catalyst, Fe / NC catalyst and Fe SAs-NC catalyst showed similar block structures with multilayer stacked block structures. However, a small amount of iron nanoparticle aggregation was found in the Fe / NC catalyst, while no obvious iron particle aggregation was found in the Fe SAs-NC catalyst, indicating that the Fe-imidazole coordination precursor suppressed the aggregation of iron ions and promoted the generation of iron single atoms.
[0070] like Figure 1 , measured using high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), found that the metal atoms exist in the form of single metals with high density, confirming the feasibility of this preparation method.
[0071] Experimental Example 2: Study on the catalytic performance of single-atom catalysts
[0072] Sulfadiazine (SDZ), a common recalcitrant micropollutant in water, was used as the research object to evaluate the catalytic performance of Fe SAs-CN catalyst for the activation of peroxymonosulfate (PMS).
[0073] Test method:
[0074] Sulfadiazine (SDZ) among the new pollutants was taken as the target pollutant, its concentration was 10 ppm, the solution volume was 50 mL, 0.2 g / L of the catalyst prepared in Examples 1-5 and Comparative Examples 1-5 was added, the concentration of potassium monopersulfate (PMS) was 0.5 mM, and the catalytic experiment was carried out without adjusting the pH. The specific test data are shown in Table 1 below.
[0075]
[0076] The degradation efficiency of SDZ by adding PMS alone was only 15.4%. Similarly, the original NC catalyst had a weak activation ability for PMS within 30 min, resulting in a low reaction rate constant (k) for SDZ degradation.
[0077] After the introduction of Fe nanoparticles into the NC catalyst (i.e., Fe / NC catalyst), the degradation efficiency of SDZ was further improved in the presence of PMS, with a reaction rate constant of 0.0210 min -1 Obviously, the Fe single atom-anchored Fe SAs-N-Cu catalyst exhibits higher SDZ degradation efficiency than the above catalysts, because the Fe single atoms in Fe SAs-NC are important PMS activation sites.
[0078] As shown in Table 1 above,
[0079] The catalysts Fe SAs-NC prepared in Examples 1-3 are 0.05 、Fe SAs-NC 0.1 and Fe SAs-NC 0.2 , among which in Fe SAs-NC 0.05 / PMS, Fe SAs-NC 0.1 / PMS and Fe SAs-NC 0.2 In the / PMS system, the degradation efficiency of SDZ within 30 min reached 86.4%, 88.6% and 92.8%, respectively. This shows that the mass ratio of iron precursor solid to melamine will affect the catalytic performance of the catalyst. When the mass ratio of iron precursor solid to melamine is 1:0.2, the catalytic efficiency of the obtained catalyst is the highest.
[0080] The difference between Example 4-5 and Example 3 is that: the mass ratio of ferrous sulfate, surfactant and 2-methylimidazole is changed; the mass ratio of methanol to ferrous sulfate and the mass ratio of surfactant sodium dodecyl sulfate and dodecyl mercaptan are changed. It is found that the mass ratio of the components has a significant effect on the catalytic performance of the catalyst. When the mass ratio of ferrous sulfate, surfactant and 2-methylimidazole is 2:8:6; the mass ratio of methanol to ferrous sulfate is 10:1; and the surfactant is sodium dodecyl sulfate and dodecyl mercaptan in a mass ratio of 4:1, the catalyst efficiency obtained is the best, especially the catalyst prepared in Example 5 can degrade SDZ by more than 99% within 30 minutes.
[0081] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a high-density N-doped carbon-based iron single-atom catalyst, characterized in that: Single atom Fe-N doped carbon catalyst (Fe SAs-NC) was synthesized by ball milling-high temperature pyrolysis method. The specific steps include: (1) adding ferrous sulfate, a surfactant, 2-methylimidazole and methanol into a ball mill and grinding to obtain an iron precursor mixture 1, centrifuging, washing and drying to obtain an iron precursor solid for later use; (2) The iron precursor solid and melamine were mixed and added to an agate bottle, and then ground and passed through a 300-350 mesh sieve to obtain a mixture; the mixture was then heated in a nitrogen atmosphere at 5°C·min -1 The mixture was heated to 600°C at a rate of 100°C and calcined for 3-6 hours to obtain a mixture 2; (3) The mixture 2 was washed with H2SO4 for 6 h to prepare a high-density N-doped carbon-based iron single atom catalyst, labeled as FeSAs-NC x ; Wherein, X is the weight ratio of the iron precursor to melamine; The surfactant is sodium lauryl sulfate and dodecyl mercaptan in a mass ratio of 3-5:1; The mass ratio of ferrous sulfate, surfactant and 2-methylimidazole in step (1) is 1-3:5-10:4-8; the mass ratio of methanol to ferrous sulfate is 8-12:1; The mass ratio of the iron precursor solid to melamine in step (2) is 1:0.05-0.
2.
2. The preparation method according to claim 1, characterized in that: The surfactant is sodium dodecyl sulfate and dodecyl mercaptan in a mass ratio of 4:
1.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the iron precursor solid to melamine in step (2) is 1:0.05, 1:0.1 or 1:0.
2.
4. A high-density N-doped carbon-based iron single-atom catalyst prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the high-density N-doped carbon-based iron single-atom catalyst prepared by the preparation method according to any one of claims 1 to 3 in the process of degrading antibiotics.
6. The use according to claim 5, characterized in that: The antibiotic is sulfadiazine.
Citation Information
Patent Citations
Monatomic catalyst for activating persulfate to generate pure singlet oxygen as well as preparation method and application thereof
CN113058635A
Fe-N4 active site monatomic catalyst for selectively generating singlet oxygen by activating peroxydisulfate as well as preparation method and application of Fe-N4 active site monatomic catalyst
CN115301268A
Cited By
Monatomic photocatalyst and preparation method and application thereof
CN122769003A